2011
DOI: 10.4103/0972-9941.78345
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of appendicular mass

Abstract: BACKGROUND:Laparoscopic appendectomy is becoming the preferred technique for treating acute appendicitis. However, its role in the treatment of complicated appendicitis is controversial. This study was undertaken to assess the feasibility of laparoscopic appendectomy for appendicular mass.MATERIALS AND METHODS:A retrospective review was performed of all the patients who were treated laparoscopically for appendicular mass from March 2007 to October 2009. Setting: Tertiary care hospital.RESULTS:A total of 120 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
2
17
1
Order By: Relevance
“…The sex ratio of 2 in our study is comparable to studies conducted by Bahram [2], Okafor & al [11] and Shinholimath & al. [13]. The average age in our study was 29 and it was similar to that of the 24 [11].…”
Section: Discussionsupporting
confidence: 61%
“…The sex ratio of 2 in our study is comparable to studies conducted by Bahram [2], Okafor & al [11] and Shinholimath & al. [13]. The average age in our study was 29 and it was similar to that of the 24 [11].…”
Section: Discussionsupporting
confidence: 61%
“…Early surgical intervention has been known to be an effective alternative to conservative therapy for a long time, as it considerably reduces the morbidity and total hospital stay, and obviates the need for a second admission. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[25] [26] [27] However, the controversy between laparoscopic appendectomy and open appendectomy for complicated appendicitis persists. [6] [27] A recent meta-analysis concluded that laparoscopic appendectomy requires signi cant resources and surgical expertise to reach maximum e ciency. Therefore, if these technical and surgical criteria cannot be met, open appendectomy should be the surgical treatment of choice.…”
Section: Discussionmentioning
confidence: 99%